Artificial Immune Systems 8th International Conference, ICARIS 2009, York, UK, August 9-12, 2009, Proceedings - Andrews, Paul S.; Timmis, Jon; Owens, Nick D. L.; Aickelin, Uwe; Hart, Emma; Hone, Andrew; Tyrrell, Andy (Theoretical Computer Science and General Issues, 2009)
This book constitutes the refereed proceedings of the 8th International Conference on Artificial Immune Systems, ICARIS 2009, held in York, United Kingdom, in August 2009. The 30 revised full papers presented were carefully reviewed and selected from 55 submissions. The papers are organized in topical sections on immune system modelling, theoretical aspects of artificial immune systems, and applied artificial immune systems. .